Can Peer Discussion Reduce Students’ Mistakes in Conceptual Physics Questions? - Japashov, Nursultan; Mansurova, Aizhan; Balta, Nuri (Pedagogika, 2023)
In this work, we tried to check whether students can overcome their mistakes in conceptual physics questions by peer discussion. For this purpose, we administered Force Concept Inventory to high school students and university students. Our study showed that high school students and university students could not overcome their mistakes in the conceptual physics questions by peer discussion. We separately found out that males are better than females at conceptual physics questions.